Getting Sick and Disabled People off Temporary Benefit Receipt: Strategies and Dilemmas in the Welfare State’s Frontline - Gjersøe, Heidi Moen (Nordic Journal of Working Life Studies, 2016)
This article explores responses by frontline workers in the Norwegian Labour and Welfare Service (NAV) to activation policy measures. Frontline workers in NAV are required to write work capability assessments for long-term sick and disabled benefit recipients within a reformed organizational structure with holistic agencies (‘one-stop shops’). These policy mechanisms are intended to empower the frontline workers and make them emphasize work and activation in their evaluation of the employability of the beneficiaries. However, a large number of long-term sick and disabled people remain in receipt of temporary benefits. Key findings emerging from this study’s fieldwork suggest that frontline workers often perceive the task of clarifying the employability status of longterm sick and disabled people to be demanding. Their assessments hinge on criteria set by actors outside the frontline office—and these criteria are hard to obtain. Consequently, the limited range of exit options restricts the discretion of the frontline workers, which results in locking claimants with complex problems into temporary benefit. Their attention tends to be drawn to concerns that are likely to be unintended, which are to keep claimants’ income safe and to secure a smooth workflow within the office as well as to smooth benefit transactions. The context of a generous welfare state with a strongly rights-based benefit scheme is regarded as a likely contributor to these concerns.